PUBLIC POLICIES FOR HIGHER EDUCATION: THE TUNING PROJECT - FIRST REFLECTIONS ON THE ADHESION OF BRAZILIAN HIGHER EDUCATION INSTITUTIONS IN THE AREA OF EDUCATION - Da Cunha, Maira Darido; Bizelli, Thais Vargas [UNESP]; Bizelli, Jose Luis [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2022)
As part of a larger project that seeks to analyze student-centered conditions in 6 South American countries, promoted by Erasmus+, the following research seeks to investigate how public Higher Education Institutions in the State of Sao Paulo have been involved with the Tuning Project, more specifically in courses aimed at teacher training. The Bologna Process emerged as a public policy within the European Union, with the aim of modernizing Higher Education curricula and internationalizing the perspective of student-centered education. In this sense, the Tuning Project and consolidates as policies that implement the Bologna Process, which, supported by the perspective of the knowledge society, aims to act as a methodology to make compatible and compare higher education, with a view to transnationalizing curricula and training labor force. work at an international level. Thus, the curricular reforms of ten Higher Education Institutions will be analyzed in order to verify the student-centered proposals. After the analysis, the information will be systematized and didactic pathways will be developed that can guide the curricular transformations in line with the methodology provided for in the Tuning Project.
Keywords: Tuning; Methodology; Higher Education Institution